Above- and belowground biomass and nutrient pools of Spartina alterniflora (smooth cordgrass) in a South American salt marsh - Negrin, Vanesa Lorena (2012)
In order to examine the role of position in the tidal range on biomass production and nutrient pools in Spartina alterniflora in an Argentinian estuary, we estimated productivity and the concentration of C, N and P in tissues and pools (concentration × biomass) of these elements in low (LM) and high (HM) zones. Aboveground biomass of S. alterniflora was higher in HM than in LM. Aboveground primary productivity was 106 and 439 g dry wt m−2 year−1 in LM and HM, respectively. Belowground biomass was similar in LM and HM. Belowground primary productivity was 526 and 744 g dry wt m−2 year−1 for LM and HM, respectively. Nutrient pools were higher in HM than in LM. Biomass and productivity values were low, which makes nutrient pools low. The lower values of the parameters analysed in LM than in HM indicate that position in the tidal range is an important factor in this system, possibly due to the effect of flooding. Moreover, this pattern is opposite to the general one observed in the northern hemisphere, meaning that studying marshes from different environments is worth doing. Because pools were higher in HM, this zone would be more important for nutrient input to the estuary.